A STUDY OF ENGAGEMENT OF THE ORGANIZATIONAL CASE STUDY IN DIGITALTV ABC - Seelueang , Piyachat; Suthammanon, Lertchai (Business Administration and Management Journal Review, 2020)
The objective of this research were to. 1.) To study the factors contributing to the level of employee engagement in the organization. 2.) To Study the relationship between engagement drivers and employee engagement level. 3.) To measure employee engagement level in the organization. 3) To apply this result study to enhance employee engagement, Case study of ABC digital TV stations. The samples used in the research were employees of ABC digital TV stations. The sample were 140 employees of ABC digital TV stations. The research instruments were the questionnaire of employee engagement . The data were analyzed by using frequency, percentage, mean and standard deviation (S.D.). The relationship between engagement drivers and employee engagement level by Pearson’s product moment correlation coefficient statistic. The research found that the highest mean was a people/Social ( = 3.94, S.D = .62), followed by job characteristics ( = 3.83, SD = 55). organization climate = 3.46, S.D = .73) and organization practice = 3.28, SD = .70) respectively. The mean of engagement were in highlevel ( = 4.00, S.D. = .52) the highest mean was in dividual perfoemance = 4.16, SD = .61), followed by team performance = 3.71, SD = .67) and organization performance = 3.39, SD = .81) respectively. The relationship between engagement drivers and employee engagement level were statistically significant at .01 level The highest correlation coefficient were organization practice (r = .801).